PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. GITA RIAU MAKMUR PEKANBARU - Wulandari, Annisa; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the effect of organizational culture and organizational commitment on employee job satisfaction at PT. Gita Riau Prosperous Pekanbaru. Organizational culture and organizational commitment as a variable (X1, X2) and employee job satisfaction as a variable (Y). The problem in this study is the occurrence of employee turnover and employee turnover is accompanied by employee absenteeism which increases every year. It can be seen from the table of turnover and company attendance. This research is a research that uses a quantitative approach. The subject of this research is PT. Gita Riau Makmur Pekanbaru with a total of 116 employees and a sample of 54 people calculated using the slovin formula. The sampling method in this study used the Accidental Sampling method, data collection using questionnaires and interviews. data analysis using SPSS. From the results of the tests conducted, it shows Organizational culture has a significant positive effect on employee job satisfaction. Organizational commitment has a significant positive effect on employee job satisfaction. Organizational culture and organizational commitment have a significant effect on employee job satisfaction.Â Keywords: Organizational Culture, Organizational Commitment and Employee Job Satisfaction